Biodegradability of degradable plastics exposed to anaerobic digested sludge and simulated landfill conditions - Shin, P.K.; Kirn, M.H.; Kim, J.M. (1997)
The biodegradabilities of various plastics by anaerobic digested sludge were measured and compared with the biodegradabilities under simulated landfill conditions. Bacterial poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHB/HV; 92/8, w/w), a natural aliphatic polyester, degraded nearly to completion within 20 days of cultivation by anaerobic digested sludge, while synthetic aliphatic polyesters such as poly-lactic acid, poly(butylene succinate), and poly(butylene succinate-co-ethylene succinate) did not degrade at all in 100 days. Cellophane, which was used as a control material, exhibited a similar degradation behavior to PHB/HV. Under simulated landfill conditions, PHB/HV degraded quite well within 6 months. Synthetic aliphatic polyesters also showed significant weight losses through 1 year of cultivation. The acidic environment inside simulators generated by the degradation of biodegradable food wastes which comprised 34% of municipal solid waste seems to cause the weight loss of synthetic aliphatic polyesters.The biodegradabilities of various plastics by anaerobic digested sludge were measured and compared with the biodegradabilities under simulated landfill conditions. Bacterial poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHB/HV; 92/8, w/w), a natural aliphatic polyester, degraded nearly to completion within 20 days of cultivation by anaerobic digested sludge, while synthetic aliphatic polyesters such as poly-lactic acid, poly(butylene succinate), and poly(butylene succinate-co-ethylene succinate) did not degrade at all in 100 days. Cellophane, which was used as a control material, exhibited a similar degradation behavior to PHB/HV. Under simulated landfill conditions, PHB/HV degraded quite well within 6 months. Synthetic aliphatic polyesters also showed significant weight losses through 1 year of cultivation. The acidic environment inside simulators generated by the degradation of biodegradable food wastes which comprised 34% of municipal solid waste seems to cause the weight loss of synthetic aliphatic polyesters.
Keywords: Natural aliphatic polyesters; Synthetic aliphatic polyesters; Anaerobic digestion; Biodegradation; Cellophane; Land fill; Sludge digestion; Polyesters; Bacteria (microorganisms)